Retinoid Signaling in Intestinal Epithelial Cells Is Essential for Early Survival From Gastrointestinal Infection - Snyder, Lindsay M.; Arora, Juhi; Kennett, Mary J.; Weaver, Veronika; Cantorna, Margherita T. (Frontiers in Immunology, 2020)
Vitamin A deficiency (A-) increases morbidity and mortality to gastrointestinal (GI) infection. Blocking retinoid signaling (dominant negative retinoic acid receptor, dnRAR) in intestinal epithelial cells (IEC, IECdnRAR) had no effect on vitamin A absorption, the expression of tight junction proteins or the integrity of the barrier. Immune cells in the gut were present in normal frequencies in the IECdnRAR mice, with the exception of the T cell receptor (TCR)αβ+/CD8αα cells, which were significantly lower than in wildtype littermates. Challenging the IECdnRAR mice with dextran sodium sulfate to induce colitis or C. rodentium infection resulted in similar disease to wildtype littermates. Feeding mice vitamin A deficient diets reduced vitamin A status and the A- IECdnRAR mice developed more severe colitis and C. rodentium infection. In particular, retinoid signaling in the IEC was crucial for the A- host to survive early infection following C. rodentium. Treating A- mice with retinoic acid (RA) beginning on the day of infection protects most mice from early lethality. However, RA treatment of the A- IECdnRAR mice was ineffective for preventing lethality following C. rodentium infection. Retionid signaling in IEC is critical, especially when there are reduced levels of dietary vitamin A. IEC are direct targets of vitamin A for mounting early defense against infection.